Global Environmental Crisis and Structural Challenges in the International System - Rahim Baizidi; Amir Abbasi Khoshkar (رهیافتهای سیاسی و بین المللی)
The global environmental crisis in the form of global warming, deforestation and increased production of industrial pollutants in the last three decades has been at the forefront of multilateral summits of developing and developing powers. Many analysts and politicians believe that one-and-a-half degree decrease in global temperature will help the preservation of the global climate diversity. Coordinated action within the framework of accepting multilateral commitments in the form of undertaking a share in reducing environmental pollutants has been the most critical solution introduced by the world powers at the 1997 Kyoto, 2015 Paris and 2021 Glasgow summits. Due to the increase in the average temperature of the Earth and the relative failure of the previous commitments of industrial powers in distancing themselves from the emission of chemical pollutants, the present essay raises the following question that what reasons contributed to the non-fulfillment of environmental obligations by the developed and developing powers? In response to this question, this hypothesis can be presented that the most prominent reasons for non-implementation of multilateral environmental agreements are the perceptual gap in the scientific and political fields, the weakness in the implementation of national environmental programs, and finally the obstruction and monopoly of financial and technological resources. It also should be noted that the current essay uses the descriptive-analytical research method; a method in which independent influential variables are examined and how their influence is explained.